Can integration reduce inequity in healthcare utilization?: evidence and hurdles in China - Zhao, Miaomiao; Liu, Baohua; Shan, Linghan; Li, Cui; Wu, Qunhong; Hao, Yanhua; Chen, Zhuo; Lan, Lan; Kang, Zheng; Liang, Libo; Ning, Ning; Jiao, Mingli (BMC, 2019)
Background: Integration of medical insurance schemes has been prioritized as one of the key strategies to address inequity in China's health system. The first pilot attempt to integrate started in 2003 and later expanded nationwide. This study aims to assess its intended impact on inequity in inpatient service utilization and identify the main determinants contributing to ieffectiveness.